Investigate the Validity, Reliability and Standardization of Family Executive Function Scale among Married People - Javanbakht, Salman; Yousefi, Zahra (Applied Family Therapy Journal (AFTJ), 2022)
Aim: The aim of this study was to evaluate the validity and reliability of the Family Executive Performance Scale among married people over 18 years of age in Isfahan. Therefore, the research was of contextualization and instrumentation. Method: This research was a survey and instrument making. The statistical population of this study consisted of all married men and women over 18 years of age in Isfahan. The statistical sample consisted of 400 men and women who were selected by convenience sampling. The research instruments included the Executive Performance Scale (GIOA, Squid, Guy and Converdie, 2000) and the Spouse Emotional Experience Questionnaire (Ghafarollahi, Yousefi, 1399). Data were analyzed in two parts: descriptive (mean and standard deviation) and inferential (Pearson correlation, Cronbach's alpha and exploratory factor analysis). Results: The results showed that internal consistency (α = 0.75), retest reliability (r = 0.450 and P